Development Of Google Form-Based Learning Outcome Evaluation Instruments For Animal Development Courses In The Biology Education Study Program FMIPA UNIMED - Nurmaya Teresia Simanullang; Herbert Sipahutar (Universitas Negeri Medan, 2023)
This study aimed to develop a valid and reliable google form-based learning outcome evaluation instrument for the Animal Development course. The instrument was developed following the 4D development model (define, design, develop, dessiminate). The research subjects were Biology Education Study Program (PSPB) class of 2021 class B students totaling 26 people. Data were obtained from validation questionnaires and student response questionnaires. The initial design of the learning outcome evaluation instrument consisted of 50 questions. Based on the validator's assessment, an instrument consisting of 25 valid and reliable questions was obtained. The results of validation by evaluation instrument experts obtained an average percentage of 98.6% with a very feasible category. Based on the validity analysis of the Aiken index, the value V = 0.942 was obtained with high validity criteria. Instrument reliability using Cronbach's Alpha obtained a value of 0.796 with high criteria (reliable), while the analysis of ICC reliability data obtained the results of inter-rater agreement of 0.796, and for each rater the consistency is 0.565. It can be concluded that the agreement between raters is very strong and each rater has a fairly good consistency. The results of the data analysis of student responses showed that each indicator was rated very well with an average percentage of 88%.theresa612